Observations of ion upflow and 630.0 nm emission during pulsating aurora - Godbole, Niharika H.; Lessard, Marc R.; Kenward, David R.; Fritz, Bruce A.; Varney, Roger. H.; Michell, Robert G.; Hampton, Don (Frontiers in Physics, 2022)
In this study, we report observations made by filtered (557.7 nm and 630.0 nm) All-Sky Imagers located at Poker Flat, Alaska alongside Poker Flat Incoherent Scatter Radar data for an event observed on February 5th, 2017. Together, the data indicate ion upflow in the vicinity of pulsating aurora. Additionally, the data show a strong 630.0 nm (red-line) auroral emission. Observations of pulsating aurora are typically reported at 557.7 nm and 427.8 nm, as these wavelengths are more sensitive to high-energy ( tens of keV) electron precipitation. In contrast, 630.0 nm emission is generated preferentially by low-energy soft electron precipitation ( hundreds of eV), and is less commonly observed. The All-Sky Imager data discussed here are unusual in that they suggest regions of enhanced soft electron precipitation in conjunction with enhanced ambipolar electric fields, which are a known factor contributing to ion outflow.